2007
DOI: 10.1074/jbc.m701857200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Inhibitors by Sortase Triggers Irreversible Modification of the Active Site

Abstract: Sortases anchor surface proteins to the cell wall of Gram-positive pathogens through recognition of specific motif sequences. Loss of sortase leads to large reductions in virulence, which identifies sortase as a target for the development of antibacterials. By screening 135,625 small molecules for inhibition, we report here that aryl (␤-amino)ethyl ketones inhibit sortase enzymes from staphylococci and bacilli. Inhibition of sortases occurs through an irreversible, covalent modification of their active site cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 53 publications
1
110
0
Order By: Relevance
“…The new 3-aminopropanamides, characterized by a quinazoline (5−7 and 11−13) or quinoline-3-carbonitrile (15−17 and 19−21) driving portion, showed inhibition of EGFR autophosphorylation in A549 cells after 1 h of incubation at 1 μM concentration, and the effect generally persisted up to 8 h after removal of the compounds from the reaction medium (Table 1). In principle, the long-lasting effect observed on EGFR autophosphorylation could be ascribed to different phenomena: (i) accumulation of the inhibitor in cells, as previously demonstrated for some reversible quinazolines; 66 (ii) conversion of the competitive inhibitor into an irreversible one at the active site of the enzyme (mechanism-based inhibition), as described for other β-aminocarbonyl compounds; 38 (iii) generation of the corresponding reactive acrylamide, as described for aryl β-aminoethyl ketones that have potential application as prodrugs of unsaturated ketones. 67 As previously described, 54,66 some reversible quinazoline EGFR inhibitors are sequestered in cells generating falsepositive results in the autophosphorylation assay based on the 8 h washout protocol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new 3-aminopropanamides, characterized by a quinazoline (5−7 and 11−13) or quinoline-3-carbonitrile (15−17 and 19−21) driving portion, showed inhibition of EGFR autophosphorylation in A549 cells after 1 h of incubation at 1 μM concentration, and the effect generally persisted up to 8 h after removal of the compounds from the reaction medium (Table 1). In principle, the long-lasting effect observed on EGFR autophosphorylation could be ascribed to different phenomena: (i) accumulation of the inhibitor in cells, as previously demonstrated for some reversible quinazolines; 66 (ii) conversion of the competitive inhibitor into an irreversible one at the active site of the enzyme (mechanism-based inhibition), as described for other β-aminocarbonyl compounds; 38 (iii) generation of the corresponding reactive acrylamide, as described for aryl β-aminoethyl ketones that have potential application as prodrugs of unsaturated ketones. 67 As previously described, 54,66 some reversible quinazoline EGFR inhibitors are sequestered in cells generating falsepositive results in the autophosphorylation assay based on the 8 h washout protocol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…38−40 These compounds possess a particular profile of reactivity, being nonreactive directly, but able to covalently modify their biological target after bioconversion via β-elimination to the corresponding α,β-unsaturated carbonyl compound. Maresso and co-workers 38 reported aryl β-aminoethyl ketones as irreversible inhibitors of the bacterial enzyme sortase, a target for the development of antibacterial therapeutics. They demonstrated through mass spectrometry and X-ray analysis that enzyme inhibition proceeds via a reactive olefin intermediate, generated in situ by amine elimination, which forms a covalent adduct with a specific cysteine residue within the protein active site.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Earlier work used in vitro (inhibition of fluorogenic substrate cleavage) and virtual screening of compound libraries to identify sortase inhibitors (15,(52)(53)(54)(55)(56). Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62). Many of the isolated compounds diminish or block staphylococcal growth, indicating that they cannot function as selective inhibitors of S. aureus sortase (53,61,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Other sortase enzymes have also been shown to possess a similar overall structure, including SrtB from S. aureus (27,35), SrtB from Bacillus anthracis (27,36), SrtA from S. pyogenes (37), and the SrtC-1 and SrtC-3 enzymes from S. pneumoniae (38). However, the molecular basis of substrate recognition remains poorly understood, because all of the structures reported to date have not contained a sorting signal bound to the enzyme.…”
mentioning
confidence: 99%